Magnetic iron oxide black for ink and preparation method and application thereof
Patent Information
- Application Number
- CN202610512043.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]为了克服现有技术中难以协同优化磁性颜料形貌、磁性能、分散性及耐热性的问题,本发明提供一种磁性油墨用氧化铁黑及其制备方法和应用,利用含氢氧化钠、硅酸钠及氧氯化锆的特定碱液实现对氧化铁黑球形形貌、低矫顽力、高分散性及优异耐热性的同步调控
[0026]1、本发明制备的氧化铁黑同步实现了规则球形形貌、低矫顽力(小于30Oe)、高比表面积(大于12m2/g)及优异的耐热性(180℃热处理30min,ΔE小于2.0)。其中,低矫顽力确保了其在磁成像等动态印刷应用中的快速磁响应与高分辨率;规则的球形形貌与精细粒径赋予了颜料优异的分散性和流动性,保障了油墨的长期储存稳定性和优异的印刷流平性,并最大限度减少对精密印刷部件的磨损;卓越的耐热性则使其能耐受高达180℃的油墨固化工艺而不变色,保证了产品批次间的一致性。这些性能精准匹配了高性能磁性油墨的苛刻需求,本发明提供的球形氧化铁黑成为制备下一代高性能磁性油墨(如高速磁成像油墨、高安全性防伪油墨)的理想磁性颜料;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of high-performance magnetic functional materials and special printing inks. Specifically, it relates to an iron oxide black for magnetic inks, its preparation method, and its application. Background Technology
[0002] Magnetic inks are functional materials that acquire magnetic responsive properties by adding magnetic pigments (such as Fe3O4) to the ink binder. Due to their ability to be automatically identified by specialized magnetic detection equipment without visual detection, magnetic inks have become indispensable key materials in fields such as bank documents (e.g., MIR codes), securities, anti-counterfeiting packaging for high-end goods, and emerging magnetic imaging digital printing. With the acceleration of digitalization and intelligentization, the market has placed higher demands on the information density, identification reliability, anti-counterfeiting level, and production efficiency of printed materials. This has led to complex requirements for the fundamental physical and chemical properties of magnetic pigments that exceed traditional standards. Among the many performance dimensions, the morphology, high-temperature stability, and dispersion behavior of magnetic pigments in the system have become key internal factors determining the printability, long-term storage stability, and consistency of the final printed product, directly affecting end applications.
[0003] Currently, iron oxide black (Fe3O4) is the most commonly used pigment in magnetic inks due to its stable chemical properties and inherent magnetism. Its conventional preparation methods include co-precipitation, hydrothermal / solvothermal methods, and microemulsion methods. Chinese invention patent CN103288140B utilizes a co-precipitation method and, by adjusting reaction conditions and additives, can easily control the morphology of nanoparticles to obtain spherical, cubic, or rod-shaped products, which provides a possibility for improving pigment dispersibility in the system. Chinese invention patent CN104495952B synthesizes octahedral iron oxide black products through a specific reaction pathway, but its morphology is difficult to meet the requirements of high-resolution printing for pigment flowability and magnetic response speed.
[0004] However, existing technologies still reveal a series of shortcomings that urgently need to be addressed when facing the complex demands of high-performance, multifunctional magnetic inks. First, most technical approaches tend to pursue the optimization of a single performance indicator in isolation, lacking a synergistic consideration of the comprehensive performance required for ink applications. Second, to achieve specific morphologies or magnetic properties, existing methods often rely on complex process conditions, expensive organic additives, or specialized equipment. This not only increases production costs but may also introduce impurities that affect the long-term stability of the ink, contradicting the direction of green and economical industrial production. Finally, a commonly overlooked but crucial issue is the heat-resistant oxidative stability of pigments. Existing technologies have failed to effectively solve the problem of Fe3O4 easily oxidizing and discoloring during subsequent high-temperature (150℃-200℃) drying or curing of inks, which seriously affects the consistency and reliability of the finished product. Summary of the Invention
[0005] To overcome the problem of difficulty in synergistically optimizing the morphology, magnetic properties, dispersibility, and heat resistance of magnetic pigments in existing technologies, this invention provides an iron oxide black for magnetic inks, its preparation method, and its application. It utilizes a specific alkaline solution containing sodium hydroxide, sodium silicate, and zirconium oxychloride to achieve simultaneous control over the spherical morphology, low coercivity, high dispersibility, and excellent heat resistance of iron oxide black.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0007] The first aspect of this invention provides a method for preparing iron oxide black for magnetic inks, comprising the following steps:
[0008] Step 1): Adjust the pH of the ferrous salt solution to 7.5-10.5 using a specific alkaline solution;
[0009] Step 2): Heat the liquid material to 50℃-90℃ using steam, and then introduce air to carry out the oxidation reaction;
[0010] Step 3): When the pH of the feed solution drops to 4.0-5.5, continue to use a specific alkaline solution to adjust the pH of the feed solution to 6.0-9.0;
[0011] Step 4): Continue to introduce air and react until the pH of the solution no longer decreases. Then, turn off the air and steam to stop the reaction.
[0012] Step 5): Rinse the liquid material, dry it, and pulverize it to obtain iron oxide black;
[0013] In steps 1) and 3), the specific alkaline solution is prepared by allowing an aqueous solution containing sodium hydroxide, zirconium oxychloride and sodium silicate to stand.
[0014] Preferably, in the specific alkaline solution, the concentration of sodium hydroxide is 2.5 mol / L-4.5 mol / L, the molar ratio of zirconium oxychloride to sodium hydroxide is 1:(50-160), and the molar ratio of sodium silicate to sodium hydroxide is 1:(35-70).
[0015] The preparation process of the specific alkaline solution includes the following steps: A sodium hydroxide solution with a concentration of 2.5 mol / L-4.5 mol / L is pre-cooled to 5℃-10℃. Zirconium oxychloride and sodium silicate are slowly added sequentially under stirring until completely dissolved. The resulting mixed solution is then allowed to stand to obtain the specific alkaline solution. The molar ratio of zirconium oxychloride to sodium hydroxide is 1:(50-160), and the molar ratio of sodium silicate to sodium hydroxide is 1:(35-70). Before adding zirconium oxychloride and sodium silicate, the sodium hydroxide solution is pre-cooled to control the dissolution rate of zirconium oxychloride in the strong alkali and prevent the formation of a precipitate.
[0016] Preferably, the settling temperature of the specific alkaline solution is 55℃-65℃.
[0017] Preferably, the specific alkaline solution is allowed to stand for at least 20 hours.
[0018] Preferably, in the ferrous salt solution of step 1), the ferrous salt is FeCl₂. 2˙ 4H₂O, Fe(NO₃) 2˙ 6H2O and FeSO 4˙ At least one of 7H2O.
[0019] Preferably, in the ferrous salt solution of step 1), the concentration of ferrous ions is 0.2 mol / L to 2.0 mol / L.
[0020] Preferably, in steps 2) and 4), the air flow rate is 10L / min-100L / min. If the air flow rate is too low, the liquid may not oxidize sufficiently; if the air flow rate is too high, the liquid may tumble and the product may agglomerate.
[0021] A second aspect of the present invention provides an iron oxide black prepared by the above-described method for preparing magnetic ink iron oxide black, wherein the iron oxide black has a regular spherical morphology, a particle size distribution D50 of 0.2 μm-0.4 μm, and a specific surface area greater than 12 m². 2 / g, coercivity less than 30 Oe, color difference ΔE less than 2.0 after heat treatment at 180℃ for 30min.
[0022] Due to its perfect spherical morphology, submicron-sized particle size, and low coercivity, this iron oxide black exhibits excellent dispersibility and stability in ink systems. It easily forms a uniform and stable composite system with resin binders. At the same time, it has extremely low wear on key components such as printing heads and doctor blades, and can meet the requirements of high-resolution magnetic imaging printing for rapid magnetic response. Moreover, after heat treatment at 180℃ for 30 minutes, the color difference ΔE of this iron oxide black is less than 2.0, and it can withstand ink curing processes at temperatures up to 180℃ without discoloration, ensuring consistency between product batches.
[0023] The third aspect of this invention provides the application of the above-mentioned iron oxide black as a core magnetic pigment in the preparation of high-performance magnetic inks.
[0024] Preferably, the magnetic ink is a high-resolution magnetic imaging printing ink, a magnetic anti-counterfeiting ink, or a magnetic recording ink. The prepared magnetic ink exhibits excellent performance in printability, storage stability, magnetic signal consistency, and high-temperature processing resistance.
[0025] The present invention, by adopting the above technical solution, has the following beneficial effects:
[0026] 1. The iron oxide black prepared by this invention simultaneously achieves a regular spherical morphology, low coercivity (less than 30 Oe), and high specific surface area (greater than 12 m²). 2 It possesses excellent heat resistance (ΔE less than 2.0 after heat treatment at 180℃ for 30 min). Its low coercivity ensures rapid magnetic response and high resolution in dynamic printing applications such as magnetic imaging; its regular spherical morphology and fine particle size endow the pigment with excellent dispersibility and flowability, ensuring long-term storage stability and excellent printing leveling properties, while minimizing wear on precision printing components; its superior heat resistance allows it to withstand ink curing processes up to 180℃ without discoloration, ensuring batch-to-batch consistency. These properties precisely match the demanding requirements of high-performance magnetic inks, making the spherical iron oxide black provided by this invention an ideal magnetic pigment for preparing next-generation high-performance magnetic inks (such as high-speed magnetic imaging inks and high-security anti-counterfeiting inks).
[0027] 2. This invention prepares a specific alkaline solution by allowing an aqueous solution containing sodium hydroxide, zirconium oxychloride, and sodium silicate to stand. Zirconate species formed by the hydrolysis of zirconium oxychloride under alkaline conditions possess strong crystal facet-selective adsorption capabilities, effectively inhibiting anisotropic crystal growth. The introduction of sodium silicate regulates the ionic strength and electric double-layer structure of the system, improving the dispersion of crystal nuclei. The synergistic effect of these two substances achieves precise control over crystal facet growth. In the specific alkaline solution, zirconium oxychloride and sodium silicate fully interact, forming a dense protective layer on the surface of Fe3O4 particles, significantly improving the thermal stability of the product.
[0028] 3. The preparation method provided by this invention is simple and mild, and can be completed under normal pressure. No organic template agent, surfactant or subsequent mechanical ball milling is required throughout the process, making it very suitable for large-scale continuous production. Attached Figure Description
[0029] Figure 1 This is a SEM image of the iron oxide black sample prepared in Example 1;
[0030] Figure 2 This is a SEM image of the iron oxide black sample prepared in Example 2;
[0031] Figure 3 This is a SEM image of the iron oxide black sample prepared in Example 3;
[0032] Figure 4 This is a SEM image of the iron oxide black sample prepared in Example 4;
[0033] Figure 5 This is a SEM image of the iron oxide black sample prepared in Example 5;
[0034] Figure 6SEM image of the iron oxide black sample prepared in Comparative Example 1;
[0035] Figure 7 SEM image of the iron oxide black sample prepared in Comparative Example 2;
[0036] Figure 8 SEM image of the iron oxide black sample prepared in Comparative Example 3;
[0037] Figure 9 SEM image of the iron oxide black sample prepared in Comparative Example 4;
[0038] Figure 10 SEM image of the iron oxide black sample prepared in Comparative Example 5;
[0039] Figure 11 SEM image of the iron oxide black sample prepared in Comparative Example 6;
[0040] Figure 12 The image shows a SEM image of the iron oxide black sample prepared in Comparative Example 7. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0042] Example 1:
[0043] (a) Preparation of specific alkaline solutions
[0044] Weigh 1000g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 10L. The concentration of sodium hydroxide at this point is 2.5mol / L. Pre-cool the resulting solution to 5℃. While stirring, slowly add 50.4g of zirconium oxychloride (using ZrOCl). 2˙ (calculated as 8H2O) and 101.6g of sodium silicate (as Na2SiO) 3˙ (Based on 9H2O), stir until completely dissolved, place the resulting mixture in a 55℃ water bath, and let it stand for 28 hours to obtain a specific alkaline solution A.
[0045] (II) Synthesis of Iron Oxide Black
[0046] 5.0 kg of solid ferrous sulfate heptahydrate was dissolved in 15 L of water to achieve a ferrous ion concentration of 1.2 mol / L. Under stirring, the specific alkali solution A prepared in step (I) was slowly added to adjust the pH of the solution to 9.5. The solution was then heated to 80 °C using steam, and air was introduced at a rate of 60 L / min for oxidation. When the pH of the solution dropped to 5.0, the pH was adjusted to 7.5 using the specific alkali solution A. Air was then introduced at a rate of 60 L / min until the pH no longer decreased, maintaining a pH of 6.4. The air and steam were then turned off, the reaction was stopped, and the solution was rinsed, dried, and pulverized to obtain the iron oxide black sample.
[0047] Example 2:
[0048] (a) Preparation of specific alkaline solutions
[0049] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 8℃. While stirring, slowly add 112.8g of zirconium oxychloride (using ZrOCl). 2˙ (calculated as 8H2O) and 100.0g of sodium silicate (as Na2SiO) 3˙ (Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 60℃ water bath and let it stand for 24 hours to obtain a specific alkaline solution B.
[0050] (II) Synthesis of Iron Oxide Black
[0051] 0.6 kg of solid ferrous chloride tetrahydrate was dissolved in 15 L of water to make the ferrous ion concentration 0.2 mol / L. Under stirring, the specific alkaline solution B prepared in step (I) was slowly added to adjust the pH of the solution to 8.5. Then, the solution was heated to 50 °C using steam, and air was introduced at 80 L / min to carry out the oxidation reaction until the pH of the solution dropped to 5.0. The pH of the solution was then adjusted to 6.3 using the specific alkaline solution B, and the reaction was continued with air introduced at 80 L / min until the pH of the solution no longer dropped. At this point, the pH of the solution was maintained at 5.3. The air and steam were turned off, the reaction was stopped, and the solution was rinsed, dried, and pulverized to obtain the iron oxide black sample.
[0052] Example 3:
[0053] (a) Preparation of specific alkaline solutions
[0054] Weigh 1800g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 10L. The concentration of sodium hydroxide at this point is 4.5mol / L. Pre-cool the resulting solution to 5℃. While stirring, slowly add 240.0g of zirconium oxychloride (using ZrOCl). 2˙ (calculated as 8H2O) and 365.4g of sodium silicate (as Na2SiO)3˙ (Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 65℃ water bath and let it stand for 20 hours to obtain a specific alkaline solution C.
[0055] (II) Synthesis of Iron Oxide Black
[0056] 8.6 kg of solid ferrous nitrate hexahydrate was dissolved in 15 L of water to achieve a ferrous ion concentration of 2.0 mol / L. Under stirring, the specific alkaline solution C prepared in step (I) was slowly added to adjust the pH of the solution to 7.5. The solution was then heated to 70 °C using steam, and air was introduced at a rate of 10 L / min for oxidation. When the pH of the solution dropped to 5.0, the pH was adjusted to 9.0 using the specific alkaline solution C. Air was then introduced at a rate of 10 L / min until the pH no longer decreased, maintaining a pH of 7.6. The air and steam were then turned off, the reaction was stopped, and the solution was rinsed, dried, and pulverized to obtain the iron oxide black sample.
[0057] Example 4:
[0058] (a) Preparation of specific alkaline solutions
[0059] Weigh 600g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.0mol / L. Pre-cool the resulting solution to 10℃. While stirring, slowly add 40.0g of zirconium oxychloride (in ZrOCl). 2˙ (calculated as 8H2O) and 77.5g of sodium silicate (as Na2SiO) 3˙ (Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 60℃ water bath and let it stand for 28 hours to obtain a specific alkaline solution D.
[0060] (II) Synthesis of Iron Oxide Black
[0061] 3.3 kg of solid ferrous sulfate heptahydrate was dissolved in 15 L of water to achieve a ferrous ion concentration of 0.8 mol / L. Under stirring, the specific alkali solution D prepared in step (I) was slowly added to adjust the pH of the solution to 10.5. The solution was then heated to 90 °C using steam, and air was introduced at a rate of 100 L / min for oxidation. When the pH of the solution dropped to 5.0, the specific alkali solution D was used to adjust the pH to 8.0. Air was then introduced at a rate of 100 L / min until the pH no longer decreased, maintaining a value of 6.4. The air and steam were then turned off, the reaction was stopped, and the solution was rinsed, dried, and pulverized to obtain the iron oxide black sample.
[0062] Example 5:
[0063] (a) Preparation of specific alkaline solutions
[0064] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 5℃. While stirring, slowly add 70.0g of zirconium oxychloride (in ZrOCl). 2˙ 87.5g of sodium silicate (calculated as Na2SiO) and 87.5g of sodium silicate (calculated as Na2SiO) 3˙ (Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 55°C water bath and let it stand for 28 hours to obtain a specific alkaline solution E.
[0065] (II) Synthesis of Iron Oxide Black
[0066] 5.0 kg of solid ferrous sulfate heptahydrate was dissolved in 15 L of water to achieve a ferrous ion concentration of 1.2 mol / L. Under stirring, the specific alkaline solution E prepared in step (I) was slowly added to adjust the pH of the solution to 9.5. The solution was then heated to 80 °C using steam, and air was introduced at a rate of 60 L / min for oxidation. When the pH of the solution dropped to 5.0, the specific alkaline solution E was used to adjust the pH back to 7.5. Air was then introduced at a rate of 60 L / min until the pH no longer decreased, at which point the pH remained at 6.4. The air and steam were then turned off, the reaction was stopped, and the solution was rinsed, dried, and pulverized to obtain the iron oxide black sample.
[0067] Comparative Example 1:
[0068] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. At this point, the concentration of sodium hydroxide is 3.5mol / L.
[0069] 5.0 kg of solid ferrous sulfate heptahydrate was dissolved in 15 L of water to achieve a ferrous ion concentration of 1.2 mol / L. A 3.5 mol / L sodium hydroxide solution was slowly added under stirring until the pH of the solution reached 9.5. The solution was then heated to 80°C using steam, and air was introduced at a flow rate of 60 L / min for oxidation until the pH dropped to approximately 5.0. The pH was then adjusted to 7.5 using the same 3.5 mol / L sodium hydroxide solution, and compressed air was continued until the pH no longer decreased, remaining at 6.4. The air and steam were then turned off, the reaction was stopped, and the solution was rinsed, dried, and pulverized to obtain the iron oxide black sample.
[0070] Comparative Example 2:
[0071] (a) Preparation of alkaline solution
[0072] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 5℃. While stirring, slowly add 70.0g of zirconium oxychloride (in ZrOCl).2˙ 87.5g of sodium silicate (calculated as Na2SiO) and 87.5g of sodium silicate (calculated as Na2SiO) 3˙ (Based on 9H2O), stir until completely dissolved, without allowing to stand, to obtain mixed alkaline solution A.
[0073] (II) Synthesis of Iron Oxide Black
[0074] In this comparative example, the synthesis steps of iron oxide black are different from those of iron oxide black in Example 5 only in that the specific alkali solution E is replaced with the mixed alkali solution A in step (I) of this comparative example. The remaining steps and raw materials are the same.
[0075] Comparative Example 3:
[0076] (a) Preparation of alkaline solution
[0077] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 5℃. Slowly add 70.0g of zirconium oxychloride (using ZrOCl) while stirring. 2˙ (Based on 8H2O), stir until completely dissolved. Place the resulting mixture in a 55℃ water bath and let it stand for 28 hours to obtain mixed alkaline solution B.
[0078] (II) Synthesis of Iron Oxide Black
[0079] In this comparative example, the synthesis steps of iron oxide black are different from those in Example 5 only in that the specific alkali solution E is replaced with the mixed alkali solution B in step (I) of this comparative example. The remaining steps and raw materials are the same.
[0080] Comparative Example 4:
[0081] (a) Preparation of alkaline solution
[0082] Weigh 700g of solid sodium hydroxide, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 5℃. Slowly add 87.5g of sodium silicate (using Na₂SiO₂) while stirring. 3˙ (Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 55℃ water bath and let it stand for 28 hours to obtain mixed alkaline solution C.
[0083] (II) Synthesis of Iron Oxide Black
[0084] In this comparative example, the synthesis steps of iron oxide black are different from those in Example 5 only in that the specific alkali solution E is replaced with the mixed alkali solution C in step (I) of this comparative example. The remaining steps and raw materials are the same.
[0085] Comparative Example 5:
[0086] (a) Preparation of alkaline solution
[0087] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 5℃. While stirring, slowly add 70.0g of zirconium oxychloride (in ZrOCl). 2˙ 87.5g of sodium silicate (calculated as Na2SiO) and 87.5g of sodium silicate (calculated as Na2SiO) 3˙ (Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 45℃ water bath and let it stand for 28 hours to obtain mixed alkaline solution D.
[0088] (II) Synthesis of Iron Oxide Black
[0089] In this comparative example, the synthesis steps of iron oxide black are different from those of iron oxide black in Example 5 only in that the specific alkali solution E is replaced with the mixed alkali solution D in step (I) of this comparative example. The remaining steps and raw materials are the same.
[0090] Comparative Example 6:
[0091] (a) Preparation of alkaline solution
[0092] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 5℃. While stirring, slowly add 70.0g of zirconium oxychloride (in ZrOCl). 2˙ 87.5g of sodium silicate (calculated as Na2SiO) and 87.5g of sodium silicate (calculated as Na2SiO) 3˙ (Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 75°C water bath and let it stand for 28 hours to obtain mixed alkaline solution E.
[0093] (II) Synthesis of Iron Oxide Black
[0094] In this comparative example, the synthesis steps of iron oxide black are different from those of iron oxide black in Example 5 only in that the specific alkali solution E is replaced with the mixed alkali solution E in step (I) of this comparative example. The remaining steps and raw materials are the same.
[0095] Comparative Example 7:
[0096] (a) Preparation of alkaline solution
[0097] Weigh 700g of sodium hydroxide solid, dissolve it in deionized water, and bring the volume to 5L. The concentration of sodium hydroxide at this point is 3.5mol / L. Pre-cool the resulting solution to 5℃. While stirring, slowly add 70.0g of zirconium oxychloride (in ZrOCl). 2˙ 87.5g of sodium silicate (calculated as Na2SiO) and 87.5g of sodium silicate (calculated as Na2SiO) 3˙(Based on 9H2O), stir until completely dissolved. Place the resulting mixture in a 55℃ water bath and let it stand for 12 hours to obtain mixed alkaline solution F.
[0098] (II) Synthesis of Iron Oxide Black
[0099] In this comparative example, the synthesis steps of iron oxide black are different from those of iron oxide black in Example 5 only in that the specific alkali solution E is replaced with the mixed alkali solution F in step (I) of this comparative example. The remaining steps and raw materials are the same.
[0100] Sample morphology and performance testing:
[0101] The morphology of the iron oxide black samples obtained in Examples 1-5 and Comparative Examples 1-7 was observed using scanning electron microscopy (SEM).
[0102] The iron oxide black samples obtained in Examples 1-5 and Comparative Examples 1-7 were tested using a vibrating-sample magnetometer (VSM) to obtain their hysteresis loops and thus coercivity data.
[0103] Particle size: determined according to national standard GB / T 19077-2024 "Particle size analysis by laser diffraction";
[0104] Specific surface area: determined according to national standard GB / T 13390-2008 "Determination of specific surface area of metal powders - nitrogen adsorption method";
[0105] Color difference value ΔE: The samples were processed according to the industry standard HG / T 3853-2006 "Determination of Heat Resistance of Pigment Dry Powder" and the color difference value ΔE of the samples before heat treatment and after heat treatment at 180℃ for 30 minutes was measured using GB / T13451.2-1992 "Determination of Relative Tinting Strength of Coloring Pigment and Relative Scattering Strength of White Pigment by Photometer".
[0106] The test results of the iron oxide black samples obtained in Examples 1-5 and Comparative Examples 1-7 are shown in Table 1 below.
[0107] Table 1: Performance test results of the iron oxide black samples prepared in Examples 1-5 and Comparative Examples 1-7
[0108] like Figure 1-5 As shown in Table 1, the iron oxide black produced in Examples 1-5 using specific alkaline solutions that meet the requirements are all regularly spherical and simultaneously possess low coercivity (<30 Oe) and high specific surface area (>12m²). 2The pigments exhibit excellent properties such as high density (g / g), submicron particle size (0.2μm-0.4μm), and excellent heat resistance (180℃ / 30min, ΔE<2.0). These performance indicators perfectly meet the requirements of high-performance magnetic inks for pigments in terms of magnetic response speed, dispersion stability, and high-temperature processing adaptability.
[0109] like Figure 6-9 As shown in Table 1, Comparative Example 1, using only sodium hydroxide solution without adding zirconium oxychloride and sodium silicate, produced a cubic product with high coercivity, low specific surface area, and poor heat resistance. Comparative Example 2, although containing zirconium oxychloride and sodium silicate, was not subjected to a settling treatment; the resulting product was also cubic, with no improvement in performance. Comparative Example 3, containing only zirconium oxychloride without sodium silicate, and Comparative Example 4, containing only sodium silicate without zirconium oxychloride, both produced cubic products with significantly inferior overall performance compared to the examples. These comparisons demonstrate that only by coexisting sodium hydroxide, zirconium oxychloride, and sodium silicate and undergoing a settling treatment can a specific alkaline solution with structure-directing function be formed, thereby obtaining spherical iron oxide black.
[0110] like Figure 10-12 As shown in Table 1, the products obtained from Comparative Example 5 (standing temperature 45℃) and Comparative Example 6 (standing temperature 75℃) both exhibit a cubic morphology, with increased coercivity, decreased specific surface area, and poorer heat resistance. This indicates that excessively low or high standing temperatures are detrimental to the sufficient interaction between zirconium oxychloride and sodium silicate. The product from Comparative Example 7 (standing time 12h) is cubic in shape, and its performance is inferior to that of the examples. Therefore, considering the results of Examples 1-5, the standing temperature is preferably controlled at 55℃-65℃, and the standing time is not less than 20h, preferably 20h-28h. Within this range, the structural guiding function of the specific alkali solution in the iron oxide black production process can be guaranteed, while also taking into account production efficiency.
[0111] In this invention, the experimental conditions of the examples are not limited to those described above. The numerical values mentioned above are reference values during the experiment and are only preferred embodiments of this invention. They are not intended to limit this invention. All modifications, substitutions, and improvements made in accordance with the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A method for preparing iron oxide black for magnetic inks, characterized in that, Includes the following steps: Step 1): Adjust the pH of the ferrous salt solution to 7.5-10.5 using a specific alkaline solution; Step 2): Heat the liquid material to 50℃-90℃ using steam, and then introduce air to carry out the oxidation reaction; Step 3): When the pH of the feed solution drops to 4.0-5.5, continue to use a specific alkaline solution to adjust the pH of the feed solution to 6.0-9.0; Step 4): Continue to introduce air and react until the pH of the solution no longer decreases. Then, turn off the air and steam to stop the reaction. Step 5): Rinse the liquid material, dry it, and pulverize it to obtain iron oxide black; In steps 1) and 3), the specific alkaline solution is prepared by allowing an aqueous solution containing sodium hydroxide, zirconium oxychloride and sodium silicate to stand.
2. The method for preparing iron oxide black for magnetic ink according to claim 1, characterized in that, In the specific alkaline solution, the concentration of sodium hydroxide is 2.5 mol / L-4.5 mol / L, the molar ratio of zirconium oxychloride to sodium hydroxide is 1:(50-160), and the molar ratio of sodium silicate to sodium hydroxide is 1:(35-70).
3. The method for preparing iron oxide black for magnetic ink according to claim 2, characterized in that, The specific alkaline solution is allowed to stand at a temperature of 55℃-65℃.
4. The method for preparing iron oxide black for magnetic ink according to claim 2, characterized in that, The specific alkaline solution shall be allowed to stand for no less than 20 hours.
5. The method for preparing iron oxide black for magnetic ink according to claim 1, characterized in that, In the ferrous salt solution of step 1), the ferrous salt is FeCl₂. 2˙ 4H₂O, Fe(NO₃) 2˙ 6H2O and FeSO 4˙ At least one of 7H2O.
6. The method for preparing iron oxide black for magnetic ink according to claim 1, characterized in that, In the ferrous salt solution of step 1), the concentration of ferrous ions is 0.2 mol / L-2.0 mol / L.
7. The method for preparing iron oxide black for magnetic ink according to claim 1, characterized in that, In steps 2) and 4), the air flow rate is 10L / min-100L / min.
8. An iron oxide black prepared by the method for preparing magnetic ink iron oxide black as described in any one of claims 1-7, characterized in that, The iron oxide black has a regular spherical morphology, with a particle size distribution D50 of 0.2 μm-0.4 μm and a specific surface area greater than 12 m². 2 / g, coercivity less than 30 Oe, color difference ΔE less than 2.0 after heat treatment at 180℃ for 30min.
9. The application of iron oxide black as a core magnetic pigment as described in claim 8 in the preparation of high-performance magnetic inks.
Citation Information
Patent Citations
A simple method for controlling the morphology of iron oxide nanoparticles
CN103288140B
A kind of preparation method of high coercive force iron black for duplicating toner
CN104495952B
